PERAN UNDANG-UNDANG NOMOR 25 TAHUN 2007 TENTANG PENANAMAN MODAL MENGATUR MENGENAI PENANAMAN MODAL DALAM NEGERI DAN PENANAMAN MODAL ASING DALAM KONTEKS PEMBANGUNAN EKONOMI NASIONAL - Mustika, Desty Anggie (YUSTISI, 2021)
The presence of law number 25 of 2007 concerning investment, in this case is the function of law as regulation, has substantially provided fresh air for investment growth in Indonesia. Various new breakthroughs regulated in this law are an effort to simplify and provide legal certainty for investors to invest in Indonesia. Of course, these conveniences are expected to attract investors to invest in Indonesia. However, all of that should still be carried out in line with the spirit of the constitution. Even though foreign investment is needed for the country's economic development, the end result must still be used for the benefit of the nation. This means that when foreign parties come to Indonesia it is hoped that they will have good intentions in order to cooperate in the economic sector. Not even detrimental to the domestic party or even more beneficial to outsiders. It is hoped that the government will not always rely solely on outside investment. Because there is a concern that this nation will always depend on the help of investors. The presence of investment, especially foreign investment, if it is too comfortable without a vigilant attitude from the government, is feared that it will create dependence on developed countries which will eventually give birth to economic colonization. For this reason, it returns to the governments of the recipient countries in directing and controlling investment, especially foreign investment so that a real contribution can be made. AbstrakKehadiran undang-undang nomor 25 tahun 2007 tentang penanaman modal dalam hal ini adalah fungsi hukum sebagai regulasi, secara substansi telah memberikan angin segar bagi pertumbuhan investasi di Indonesia. Berbagai terobosan baru yang diatur dalam undang-undang ini merupakan upaya untuk mempermudah dan memberikan kepastian hukum bagi para pemodal untuk menanamkan modalnya di Indonesia. Kemudahan-kemudahan ini tentunya diharapkan dapat menarik investor agar mau berinvestasi di Indonesia. Namun hendaknya semua itu tetap dilaksanakan dengan sejalan semangat konstitusi. Meskipun penanaman modal asing diperlukan guna pembangunan ekonomi negara tetapi hasil akhirnya nanti tetaplah harus dimanfaatkan guna kepentingan bangsa. Artinya ketika pihak asing yang datang ke Indonesia diharapkan mereka benar-benar bertujuan baik dalam rangka melakukan kerja sama di bidang perekonomian. Bukan malah merugikan pihak dalam negeri atau malah lebih menguntungkan pihak luar. Diharapkan pemerintah juga tidak semata-mata selalu mengandalkan dari investasi pihak luar. Sebab akan dikhawatirkan bangsa ini akan selalu ketergantungan dengan bantuan investor. Kehadiran penanaman modal, khususnya penanaman modal asing apabila terlalu nyaman tanpa ada sikap waspada dari pemerintah dikhawatirkan akan menciptakan ketergantungan kepada negara-negara maju yang pada akhirnya melahirkan penjajahan ekonomi. Untuk itu, kembali lagi kepada pemerintah negara penerima modal dalam mengarahkan dan mengendalikan penanaman modal khususnya penanaman modal asing agar kontribusi nyata dapat diberikan.